Strong and Robust Polyaniline‐Based Supramolecular Hydrogels for Flexible Supercapacitors. (22nd June 2016) - Li, Wanwan; Gao, Fengxian; Wang, Xiaoqian; Zhang, Ning; Ma, Mingming
Abstract: We report a supramolecular strategy to prepare conductive hydrogels with outstanding mechanical and electrochemical properties, which are utilized for flexible solid‐state supercapacitors (SCs) with high performance. The supramolecular assembly of polyaniline and polyvinyl alcohol through dynamic boronate bond yields the polyaniline–polyvinyl alcohol hydrogel (PPH), which shows remarkable tensile strength (5.3 MPa) and electrochemical capacitance (928 F g −1 ). The flexible solid‐state supercapacitor based on PPH provides a large capacitance (306 mF cm −2 and 153 F g −1 ) and a high energy density of 13.6 Wh kg −1, superior to other flexible supercapacitors. The robustness of the PPH‐based supercapacitor is demonstrated by the 100 % capacitance retention after 1000 mechanical folding cycles, and the 90 % capacitance retention after 1000 galvanostatic charge–discharge cycles. The high activity and robustness enable the PPH‐based supercapacitor as a promising power device for flexible electronics.